Determination Of Baseline Qualities Of Malaysian Export-Grade Starfruits - Hashim, Norhashila (2008)

(untitled)
A study was conducted to determine the baseline qualities of Malaysian export-grade strafruits. The study is focused on the B10 cultivar of starfruits for the range of colour indexes between 2 and 4, targeted for the export market. A total of 123 commercially-graded, B10 cultivar starfruits were selected randomly and their properties namely length, diameter, mass, volume, the five colours values (L, a*, b*, C, ho), firmness, TSS (Total Soluble Solids), TA (Titratable Acidity) and pH were measured directly. From these properties, further properties were derived by calculation to make up a total of 31 properties investigated. Outlier analysis was conducted and four outliers identified by samples number 94, 95, 97, and 109 were eliminated. Therefore, the remaining samples for further analyses became 119. Studies on these 119 samples show that the properties length, diameter, mass and hue have low coefficient of variation (CV) levels. The fact that the starfruits were the actual marketable products indicates that mass and hue are sufficient element for quality indicators. Mass and hue were 15th and 3rd respectively in ranking by CV. Correlation studies revealed that mass has a very strong correlation with volume while hue has strong correlation with firmness. The property, pH, could be predicted moderately by b*. Since the study was conducted on export-grade starfruits, the minimum values can be taken as baseline values for acceptance of export-grade starfruits.